2008
DOI: 10.1177/112067210801800106
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Central Corneal Thickness and Parameters of Optic Nerve Head Topography in Healthy Subjects

Abstract: In addition to its effect in the accuracy of intraocular pressure measurements, CCT has a structural relationship with the ONH in healthy nonglaucomatous eyes. Therefore, its effect on disc area might be especially important to explain the structural strength of the ONH in the pathogenesis of glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 30 publications
3
9
2
Order By: Relevance
“…They found smaller disc areas (1.83±0.35 mm 2 ) and smaller rim areas (1.27 mm 2 ) and slightly larger CDR (0.51±0.16) compared with our study. Large studies (n4100) that measured normal disc size using Stratus OCT 10,[21][22][23][24][25] have reported disc areas between 2.34 ± 0.41 and 2.63 ± 0.55 mm 2 , which are larger than our value of 1.98 ± 0.38 mm 2 . These studies also report cup-disc area ratios between 0.17 ± 0.11 and 0.37 ± 0.20, which are substantially smaller than our value of 0.44±0.18.…”
Section: Eyecontrasting
confidence: 53%
“…They found smaller disc areas (1.83±0.35 mm 2 ) and smaller rim areas (1.27 mm 2 ) and slightly larger CDR (0.51±0.16) compared with our study. Large studies (n4100) that measured normal disc size using Stratus OCT 10,[21][22][23][24][25] have reported disc areas between 2.34 ± 0.41 and 2.63 ± 0.55 mm 2 , which are larger than our value of 1.98 ± 0.38 mm 2 . These studies also report cup-disc area ratios between 0.17 ± 0.11 and 0.37 ± 0.20, which are substantially smaller than our value of 0.44±0.18.…”
Section: Eyecontrasting
confidence: 53%
“…A biological link may exist between aspects of the cornea that regulate its thickness and the physical and structural properties of tissues involved in glaucoma pathogenesis, most notably the optic disc and lamina cribrosa. Several studies have found an association with CCT and various physical parameters of the optic disc, including disc area88 89 and depth of the cup 90. These findings are in contrast to those of Nicolela et al 91 and Wells et al 92 and who found no correlation between CCT and the optic disc rim area or cup depth.…”
Section: Why Study the Genetics Of Cct?mentioning
confidence: 85%
“…Many reports have suggested that the cornea is related to the optic nerve in some way; some clinicians have looked for a relationship between glaucoma and CCT. [7][8][9][10]18 A recent study found that CCT is not related to the risk of developing a glaucomatous visual field loss or progression, 19 and a histomorphometric study failed to find an association between CCT and the thickness of the lamina cribrosa. 12,20 However, these results did not provide a definitive answer regarding the relationship between the cornea and the optic disc.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that thin corneas may have an association with weak optic nerve heads and that this may be related to a thin lamina cribrosa. 7,8 Furthermore, some studies have shown that the development and progression of glaucoma correlates with central corneal thickness; 9 other studies refute this claim. 10,11 Wells et al 11 insisted that corneal hysteresis, but not corneal thickness, correlates with the vulnerability of the optic nerve surface.…”
Section: Introductionmentioning
confidence: 94%